Does anemia impact hospital readmissions after coronary artery bypass surgery?. Issue 8 (11th December 2012) - Shehata, Nadine; Forster, Alan; Li, Le; Rothwell, Deanna M.; Mazer, C. David; Naglie, Gary; Fowler, Robert; Tu, Jack V.; Rubens, Fraser D.; Hawken, Steven; Wilson, Kumanan
<x xml:space="preserve">Abstract</x> Background Anemia is one of the most common complications of coronary artery bypass graft (CABG) surgery and has been shown to be associated with increased morbidity and mortality. The impact of anemia on hospital readmission after CABG, a potential measure of delayed complications, has not been addressed. Study Design and Methods We conducted a single‐center retrospective study of 2102 patients who had CABG in Ontario to determine whether anemia at hospital discharge was associated with increased 30‐day hospital readmissions, readmission secondary to cardiac disease, and 30‐day mortality using administrative data. Results Of the 2102 patients, 224 patients (11%) were readmitted within 30 days of hospital discharge. Infection was the leading cause of readmissions (24%), followed by heart failure (13%), pulmonary disease (7%), and hemorrhagic disease (7%). Overall, 2.6% of patients were readmitted because of cardiac disease. Of patients discharged, 48% were discharged with a hemoglobin (Hb) level between 8 and 10 g/dL and 42% between 10 and 12 g/dL. Predischarge Hb concentration was not a significant independent predictor of 30‐day readmission to the hospital due to all causes, readmission to the hospital due to cardiac causes, or 30‐day mortality. A higher comorbidity score, adjusted odds ratio (OR) of 2.1 (95% confidence interval [CI], 1.3‐3.6), leg and sternal wound infections OR of 1.9 (95% CI, 1.2‐3.0), and postoperative renal failure OR of 1.4 (95% CI, 1.2‐2.0) were associated with increased 30‐day readmission rates. Conclusions The predischarge Hb concentration after CABG was not associated with 30‐day readmissions.